The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/pon.922
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impacts of a camping experience for children with cancer and their siblings

Abstract: Expectations appear substantially different for patient versus sibling campers. The camping experience appeared to impact these groups differently, with patient campers impacted in ways not experienced by sibling campers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…Following camp attendance, researchers have observed better attitudes toward their illnesses and lower levels of trait anxiety in children with asthma, diabetes, and spina bifida (Briery & Rabian ); improved affect has been noted in children with cancer (Wellisch et al . ). Youth with HIV/AIDS formed caring connections, felt reprieve and recreation, and increased their illness related knowledge, positive attitudes, and conflict resolution skills as a result of attending summer camp (Gillard et al .…”
Section: Introductionmentioning
confidence: 97%
“…Following camp attendance, researchers have observed better attitudes toward their illnesses and lower levels of trait anxiety in children with asthma, diabetes, and spina bifida (Briery & Rabian ); improved affect has been noted in children with cancer (Wellisch et al . ). Youth with HIV/AIDS formed caring connections, felt reprieve and recreation, and increased their illness related knowledge, positive attitudes, and conflict resolution skills as a result of attending summer camp (Gillard et al .…”
Section: Introductionmentioning
confidence: 97%
“…1,11,12 Although it is commonly agreed by burn care professionals that burn camps are beneficial and that more especially the campers themselves and their parents see camps as a positive experience, very little empirical evidence for this has until now been found in international literature. As in the case of other pediatric camps, 13 small sample sizes and a possible cumulative effect of attending consecutive burn camps also hamper the measurement of the clear effects of burn camps. Furthermore, most reports are descriptive in nature.…”
mentioning
confidence: 94%
“…Most of this research examines camps as leisure services (Apter, 1977;Emira & Thompson, 2011;Huber, Walsh, & Varman 2005;Jeanes & Magee, 2012;Sullivan, Ward, & Deutsch, 2010;Taber & Proch, 1988). There have also been studies looking at specialized camps, including ones for children with hemophilia (Thomas & Gaslin, 2001), cancer (Mosher, 2006;Wellisch, Crater, Wiley, Belin, & Weinstein, 2006), diabetes (Hunter, Rosnov, Koontz, & Roberts, 2006), vision impairment (Day & Kleinschmidt 2005), and chronic diseases (Bekesi et al, 2011). More important for this research, we have found that there are no studies focused on family camping as a highly valued leisure experience.…”
Section: Review Of the Literaturementioning
confidence: 78%